(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2020)
As a consequence of the current stage of the no-tilage System, some inherent problems are evident, in which soil compaction is highlighted in the surface layer. However, structural soil quality is desirable for plant growth, as well as establishment of the root system. The objective of this study was to evaluate the root distribution of soybean, tensile strength and friability of soil aggregates in different management systems with the application of agricultural gypsum and the use of fixed shanks for deep action in seed drill. The experimental design consisted of a 2x2x2 factorial arrangement, arranged in randomized blocks with three replicates. In the R2 stage of the soybean, the soil was collected for evaluation of the root system at depths of 0.0-0.05, 0.05-0.10, 0.10-0.20, 0.20-0, 40 and 0.40-0.60 m, and the values ​​of diameter (mm) and length (cm) were quantified by SAFIRA software. To determine the tensile strength and friability, soil monoliths were collected in the trench wall in the 0.0-0.2 m layers. Statistical analyzes were performed using the Sisvar 5.3 program. The scarification of the soil followed by the use of the furrowing rod resulted in losses in the physical quality of the soil, reducing the friability of the aggregates, and allowing a greater density of the root length (cm cm-3) in the layer 0,0-0,20. The no-tillage system provided a higher density of root length (cm cm-3) in subsurface layers (0.20-0.40). The application of gypsum did not alter the tensile strength and friability of the soil aggregates. The use of the furrowing rod in the planter provided a reduction in tensile strength values ​​and friability.